Optimization of medical and surgical care for congenital heart defects in children (Bangladesh Journal of Medical Science, 2026)
In a review of the literature discussed the organization of medical care for children with congenital heart disease; especially natural course of the disease; quality of life and social aspects; rehabilitation of patients. According to published research articles and monographs on the problems of congenital heart defects in children, it concluded that, despite the high achievement of modern medicine in this area, are still not fully explored optimitsatsiya medical care with congenital heart disease and as a consequence, improve the quality and duration of their life. An article is considered the analysis of frequency of congenital heart diseases (CHD) at the newborns that were on treatment in the regional perinatal center of the South Region Kazakhstan for 5 years (2020- 2024). Frequency of all heart diseases on the average has 9,1 to 1000, counting on children population. In the structure of pathology there are prevailed: ventricular septal defect, atrial septal defect, patent ductus arteriosus and pulmonary artery stenosis. By last years the quantity of the non correlated valvular defects are increased considerably. It is important to take into account this circumstance in clinical practice. There are reflected the features of the natural history of congenital heart diseases with a high lethality at children, especially in the first year of life.BJMS, Vol. 25 No. 01 January’26 Page : 68-77